Al Qaeda in the Islamic Maghreb: Terrorism, insurgency, or organized crime?. (2nd September 2016) - Boeke, Sergei
Abstract: After incurring significant losses during France's 2013 Operation Serval in Mali, Al Qaeda in the Islamic Maghreb (AQIM) is back. Mokhtar Belmokhtar has rejoined the group, violent attacks are on the increase, and southern Libya offers elements of the group a new safe-haven. This article takes a long view on AQIM, looking at its objectives and ideology, organizational structure, relationship with the local population and revenue model to determine whether they should be labelled as terrorists, insurgents, or ordinary criminals. The article concludes that AQIM generally follows a strategy of terrorism, while some elements and modus operandi could also be indicative of a strategy of insurgency. AQIM's primary commanders have a long-standing relationship with the global Al Qaeda movement, are unlikely to be seduced by the Islamic State, and enjoy significant autonomy in conducting their operations. There is, however, little evidence that supports the view that AQIM is a criminal organization behind a religious façade, and its Salafi–jihadist ideology remains a leading determinant.